Quranic Foundations for Dialogue with Others - Ahmad Qusyairi Suhail (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
This study explores the vital role of dialogue in human life, presenting it as a human necessity, a religious obligation, and a contemporary demand. From the Qur’anic perspective, dialogue is not merely a form of communication, but also a method of imparting knowledge, a means of da'wah (Islamic propagation), and a key strategy for peaceful coexistence. The objective of this research is to analyze the Qur’anic foundations of dialogue and identify the guiding principles for engaging with others. A qualitative methodology is adopted, utilizing library research and content analysis of Qur’anic verses that involve dialogue. The findings reveal that the Qur’an promotes dialogue as a core method for social engagement and da'wah, even in matters of creed and belief. It emphasizes recognition of the other, affirms difference as a divine law, and advocates for reasoned, ethical, and informed discourse. The implications suggest that Muslims should prioritize dialogue to counter modern challenges such as Islamophobia and religious conflicts, and to foster a culture of tolerance and mutual respect.